The role of obstetric nurses in non-pharmacological methods of pain relief during labor (Research, Society and Development, 2025)
Introduction: Childbirth brings new sensations and experiences that are described as a unique experience directly linked to its occurrence and the moments before and after birth. Nurses can use non-pharmacological methods for labor pain relief. Objective: To discuss nurses' role in using non-pharmacological methods for labor pain relief. Methodology: This integrative review found 10,788 articles, available in Portuguese and English, published in databases from 2018 to 2022, using indicators. These articles were filtered, and eight met the inclusion criteria. The Virtual Health Library (VHL) searched these databases: LILACS, BDENF, and MEDLINE. Discussion: This process evaluated the benefits of using non-pharmacological methods for labor pain relief, demonstrating through scientific evidence that their use is more effective than using no method, placebo, or any other. Conclusion: It was observed that the use of non-pharmacological methods by obstetric nurses is essential for the support and control of pain in the parturition process, as they are important assistance tools that ensure good practices and humanization of the assistance provided to the woman, the conceptus and the family.